Legal Analysis of the Regulation of Legal Liability for Violations of the Law by Motorized Vehicle Owners - Purwantono, Rivan Achmad; Gunarto, Gunarto; Tri Bawono, Bambang (Universitas Islam Sultan Agung, 2023)
Based on the provisions of Article 14 in PP No. 18 of 1965 which regulates the liability of motorized vehicle owners in Indonesia, its implementation to date has not been fully realized. This is due to the complexity of the legal subjects responsible for the implementation of these provisions, which causes injustice to motorized vehicle owners. In certain situations, vehicle owners are not involved in an accident at all, as the vehicle is under their control. The core cause of this problem lies in the vagueness of the applicable regulations, which do not explicitly distinguish between individual and collective responsibility for traffic accidents. Therefore, research was sought to reconstruct the relevant norms, rules and regulations so that the implementation of Article 14 in PP No. 18 of 1965 can be carried out effectively. Several other regulations, including but not limited to Act No. 22 of 2009 and related regulations, have accommodated provisions regarding traffic law violations and accidents comprehensively. The results show that there was injustice for motorized vehicle owners because the accident did not occur when the vehicle was under their control. The arrangements in other regulations also indicated that the party who must be responsible for a traffic accident is the driver of the vehicle that caused the accident, regardless of his status as a vehicle owner or not. This phenomenon occurred due to the failure to clearly separate individual and collective responsibility for traffic accidents in the context of Article 14-PP No. 18 of 1965. In an effort to achieve balanced and accurate legal justice, it is necessary to revise and improve the relevant regulations to ensure a balance in the determination of responsibility in traffic accident cases.